Kecemasan Menjalin Relasi Romantis: Studi Kasus terhadap Perempuan Penyintas Toxic relationship - Anindya Rahmawati Putri; Yudi Kurniawan (Philanthropy: Journal of Psychology, 2023)
Abstract. This study aims to find out empirically anxiety in undergoing romantic relationships among women survivors of toxic relationships and what are the factors that influence anxiety in undergoing romantic relationships among women survivors of toxic relationships. The research method chosen was qualitative research with data collection techniques consisting of interviews and observation. Respondents in this study amounted to 3 respondents with the criteria of female students who are currently studying at both public and private universities, age range 20 to 22, are not currently in a romantic relationship, and have had a toxic relationship in a romantic relationship for at least one year. , and found the dynamics of anxiety in the subject. The results found in this study are toxic relationships in undergoing romantic relationships with forms of physical, psychological, sexual and financial or economic violence can cause a negative impact on the survivor's psychology in the form of anxiety caused by bad past experiences and anxiety about the relationship that will come.Keywords: Anxiety, Toxic relationship, Survivor, Romantic RelationshipAbstrak. Penelitian ini bertujuan untuk mengetahui secara empiris kecemasan dalam menjalani relasi romantis pada perempuan penyintas toxic relationship dan apa saja faktor yang memengaruhi kecemasan dalam menjalani relasi romantis pada perempuan penyintas toxic relationship.  Dengan metode penelitian yang dipilih adalah penelitian kualitatif dengan teknik pengumpulan data adalah wawancara dan observasi. Responden dalam penelitian ini berjumlah 3 responden dengan kriteria mahasiswi yang tengah menempuh pendidikan baik di universitas negeri maupun swasta, rentang usia 20 hingga 22, sedang tidak dalam status menjalin hubungan relasi romantis, dan pernah menjalani toxic relationship dalam relasi romantis pada kurun waktu minimal satu tahun, serta ditemukan dinamika kecemasan pada subjek. Hasil yang ditemukan pada penelitian ini adalah toxic relationship dalam menjalani relasi romantis dengan bentuk kekerasan fisik, psikis, seksual dan finansial atau ekonomi dapat menyebabkan dampak negatif pada psikis penyintas nya berupa kecemasan yang dikarenakan oleh pengalaman masa lalu yang buruk dan rasa cemas mengenai hubungan yang akan datang.Kata kunci: Kecemasan, Toxic relationship, Penyintas, Relasi Romantis